Analyzing consumer willingness to pay for organic extra virgin olive oil: A logit model approach - Lanfranchi, Maurizio; Algeri, Carmelo; Dimitrova, Vihra; Pascale, Angelina De; Giannetto, Carlo (International Journal of Innovative Research and Scientific Studies, 2024)
The present study examines the elements that influence Italians' willingness to pay a higher price for organic olive oil. As a result, a survey was conducted involving a heterogeneous sample of 332 consumers and their propensity to spend a surplus price was examined using a logit model. According to the study findings, consumers are willing to pay more for organic olive oil and this willingness to pay increases with age, education level, living in a smaller household, consumption of organic food and traditional sources such as producers, retailers and supermarkets. The empirical investigation demonstrates the convenience for farms of converting olive oil production from conventional to organic in order to fulfill customer needs. Companies are able to plan their medium-and long-term commercial activities when they can predict customer preferences. Indeed, consumer information may have a beneficial effect on the community as a whole due to the considerable quantity of positive environmental externalities associated with organic olive production.